The influence of gadgets on social development of pre-school children in village iv jalan rejo, paya lombang sub-district, tebing high district, serdang bedagai district year 2022 - Rosmani Sinaga (Science Midwifery, 2022)
Gadgets have positive things for children, they can be interesting learning media for children but the negative impacts of using gadgets are delays in language, attention disorders, problems in learning, anxiety, and can cause depression in children, and social behavior that causes depression. disorders in children (Sundus, 2018). Based on UNICEF data, it shows that the incidence of growth and development disorders in children is still high as much as 27.5% or equivalent to three million children experiencing disorders, more than 200 million children fail to reach their potential in development, more in developing countries including Indonesia (Riskesdas, 2018) This type of research uses a research using a questionnaire in assessing the influence of gadgets on the development and social interaction of preschool children 4-6 years.The results of the study based on respondents were in the Education group that the most were in high school as many as 19 people (59.4%) when compared to the first category, third and fourth namely junior high school as many as 5 (15.6%), D3 as many as 5 (15.6%) and Bachelor as many as 3 people (9.4%). Then on the job characteristics of the most respondents, namely IRT as many as 17 people (53.1%) when compared to the second category, and third, namely employees as much as 2 (6.3%), and entrepreneurs as many as 13 (40.6%). Finally, on the characteristics of the child's age, the most respondents were at the age of 6 years as many as 17 people (53.1%) when compared to the first and second categories, namely employees as many as 6 (25.0%) and 7 (21.9%).